Weight reduction added to CPAP decreases blood pressure and triglyceride level in OSA: Systematic review and meta‐analysis. Issue 5 (24th February 2022) - Kovács, Dóra K.; Gede, Noémi; Szabó, László; Hegyi, Péter; Szakács, Zsolt; Faludi, Béla; Sebők, Ágnes; Garami, András; Solymár, Margit; Kósa, Dániel; Hanák, Lilla; Rumbus, Zoltán; et al.
Abstract: Obstructive sleep apnea (OSA) is associated with treatment‐resistant hypertension and high cardiovascular risk. Continuous positive airway pressure (CPAP) fails to reduce cardiovascular risks consistently. Obesity and OSA show reciprocal association and they synergistically increase hypertension via different pathways. Our meta‐analysis aimed to assess the cardiovascular benefits of combining weight loss (WL) with CPAP (vs. WL or CPAP alone) in OSA. Outcomes included systolic and diastolic blood pressure (BP) and blood lipid parameters. We explored Medline, Embase, Cochrane, and Scopus. Eight randomized controlled studies (2627 patients) were included. The combined therapy decreased systolic BP more than CPAP alone. Weighted mean difference (WMD) for CPAP + WL versus CPAP was −8.89 mmHg, 95% confidence interval (95% CI; −13.67 to −4.10, p  < 0.001) for systolic BP. For diastolic BP, this decrease was not significant. In case of blood lipids, the combined treatment decreased triglyceride levels more than CPAP alone (WMD = −0.31, 95% CI −0.58 to −0.04, p  = 0.027). On the other hand, addition of CPAP to WL failed to suppress BP further. The certainty of evidence according to GRADE was very low to moderate. In conclusion, our results showed that the addition of WL to CPAP significantly improved BP and blood lipid values in OSA. On the other hand, the addition of CPAP to WL could not significantly improve BP or blood lipid values. Review protocol: PROSPERO CRD42019138998.